VD_FINDINFO AI 34/09 - 99/2010 vom 15. März 2010 - VD Tribunal cantonal (2010)
FORCE PROBANTE, EXPERTISE MÉDICALE, PRESTATION D'ASSURANCEAI | 1 LAI, 28 LAI, 4 al. 1 LAI, 56 LPGA, 58 LPGA, 6 LPGA, 60 al. 1 LPGA, 7 LPGA, 8 al. 1 LPGA